Efficacy of Health Literacy Interventions for Caregivers of Individuals with Neurodevelopmental and Chronic Conditions: A Rapid Review - Thom Nevill; Jessica Keeley; Susan Hunt; Rachel Skoss; Olivia Lindly; Jenny Downs; Amanda Marie Blackmore (Children)
Background/Objectives: Caregivers of individuals with neurodevelopmental and chronic health conditions require health literacy (HL) skills for the long-term management of these conditions. The aim of this rapid review was to investigate the efficacy of HL interventions for these caregivers. Methods: Five databases (Cochrane Central, PubMed, Embase, CINAHL, and PsycINFO) were searched. Studies were eligible for inclusion if they reported the efficacy of any intervention aimed at improving the HL of caregivers of individuals with a neurodevelopmental disorder or chronic condition and assessed caregiver HL. All original intervention study designs were eligible, as were systematic reviews. Studies had to be published in English since 2000; grey literature was excluded. The review was registered before commencement with PROSPERO (CRD42023471833). Results: There were 3389 unique records, of which 28 papers (reporting 26 studies) were included. In these studies, 2232 caregivers received interventions through a wide range of media (online, group, written materials, one-to-one, video, phone, and text messages). Research designs were classified as Levels I (n = 8), II (n = 5), III (n = 2), and IV (n = 11), and the quality of evidence ranged from high to very low. Half (n = 7) of the trials with moderate to high evidence levels reported significant between-group differences in caregiver HL outcomes and/or individuals’ health-related outcomes. Effective interventions occurred across a wide range of conditions, ages, and carer education levels and using a diversity of intervention media. Conclusions: HL interventions for caregivers of individuals with neurodevelopmental and chronic conditions can improve health-related outcomes and caregivers’ HL. Longer and more intensive HL programs may be more likely to be effective, but attention must be paid to participant retention.